2020
DOI: 10.1210/jendso/bvaa046.690
|View full text |Cite
|
Sign up to set email alerts
|

MON-176 Discovery and Identification of Late Stage Selective Nonpeptide ACTH Antagonists for the Treatment of Cushing’s Disease, Ectopic ACTH Secreting Tumors, and Congenital Adrenal Hyperplasia

Abstract: Adrenocorticotropic hormone (ACTH) is an important modulator of steroidal hormone synthesis and secretion from the adrenal gland and its selective activity at the melanocortin type 2 receptor (MC2) dictates the synthesis and secretion of cortisol (corticosterone in rats). Excess ACTH action contribute to the pathophysiology of Cushing’s disease (CD), ectopic ACTH secreting tumors (EAS), and Congenital Adrenal Hyperplasia (CAH). Cushing’s disease results from a microadenoma derived from pituitary corticotrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In vivo studies have been performed in dogs and rodents that demonstrated good oral bioavailability. Efficacy studies in rats demonstrated dose-dependent acute suppression of plasma levels of corticosterone and reversal of the sustained ACTH exposure-induced phenotype and adrenal hypertrophy 137 , 138 . These promising preclinical results have led to the investigation of CRN04894, an oral MC2R antagonist, in a double-blind, randomized, placebo-controlled phase I study 139 .…”
Section: Novel Therapiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In vivo studies have been performed in dogs and rodents that demonstrated good oral bioavailability. Efficacy studies in rats demonstrated dose-dependent acute suppression of plasma levels of corticosterone and reversal of the sustained ACTH exposure-induced phenotype and adrenal hypertrophy 137 , 138 . These promising preclinical results have led to the investigation of CRN04894, an oral MC2R antagonist, in a double-blind, randomized, placebo-controlled phase I study 139 .…”
Section: Novel Therapiesmentioning
confidence: 99%
“…Hypothalamic–pituitary–adrenal axis suppressors Corticotropin-releasing factor receptor 1 (CRF1) antagonist, crinecerfont 126 – 129 : currently ongoing phase III trials CRF1 antagonist, tildacerfont 130 – 133 : currently ongoing phase II trials Adrenocorticotrophic hormone (ACTH) antagonist, ALD1613 (monoclonal antibody) 134 , 135 : about to enter phase I trials ACTH receptor (melanocortin type 2 receptor; MC2R) antagonist, CRN04894 (refs 137 – 139 ): currently ongoing phase I trials …”
Section: Novel Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, many challenges related to treatment remain. Managing patients with 21-OHD using glucocorticoids (GCs) is not optimal, and additional treatments have been proposed ( 3 5 ), such as the androgen antagonist, flutamide; the aromatase inhibitor, testolactone; the P450c17 inhibitor, abiraterone acetate ( 6 , 7 ); the corticotropin-releasing factors, receptor 1 antagonist crinecerfont ( 8 , 9 ) and tildacerfont ( 10 ); ACTH antagonists ( 11 , 12 ); and melanocortin type 2 receptor antagonist ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%